2000
DOI: 10.1046/j.1469-0705.2000.00006.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood flow velocity waveforms from fetal peripheral pulmonary arteries in pregnancies with preterm premature rupture of the membranes: relationship with pulmonary hypoplasia

Abstract: The measurement of peripheral pulmonary velocity waveforms may help to establish the risk of developing pulmonary hypoplasia in pregnancies complicated by premature rupture of membranes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 24 publications
2
14
0
Order By: Relevance
“…Figure 1 summarizes the identification and selection process of the thirteen published studies included in this meta‐analysis12–24. All studies reported on ultrasound parameters, and one also evaluated (two‐dimensional) MRI parameters.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 summarizes the identification and selection process of the thirteen published studies included in this meta‐analysis12–24. All studies reported on ultrasound parameters, and one also evaluated (two‐dimensional) MRI parameters.…”
Section: Resultsmentioning
confidence: 99%
“…PPROM may cause adverse outcomes via oligohydramnios, which in turn leads to pulmonary hypoplasia and pulmonary artery musculature hyperplasia 10 2224. Postnatally this leads to difficulties with ventilation, including air leak, pulmonary hypertension and severe hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…Over a period of weeks, the lungs fail to grow in pace with the remainder of the fetus. This is manifest on ultrasound as a lag in chest circumference, chest-abdomen ratio, or lung length, among other indirect parameters of pulmonary growth [15,33,34]. Because the lag in lung growth likely reflects the results of an earlier insult rather than an ongoing process, it is unlikely that earlier delivery enhances outcome once pulmonary hypoplasia is suspected.…”
Section: How Does Pulmonary Hypoplasia Occur and How Is It Diagnosed?mentioning
confidence: 99%